Cultural treatments and woody debris: the study case of beech forests in Casentino (Italy) - Calamini G; Bianchi L; Salvadori G (Forest@, 2009)
This paper shows the first results about quantity and quality of dead wood on the ground in beech forests of Foreste Casentinesi, Monte Falterona and Campigna National Park. The presence of dead wood depends on several factors such as forest productivity, natural disturbances and human activities. Data from some mature managed beech stands have been collected and compared with those from unmanaged beech forest (Sasso Fratino full-protected Reserve). Results do not show significant differences between managed and unmanaged forests. The dead wood varies between 5 and 8 Mg ha-1 (in terms of total dry weight) mostly composed by fine woody debris.